2016
DOI: 10.1371/journal.pone.0160355
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of FosB Proteins and Potential Target Genes in Select Brain Regions of Addiction and Depression Patients

Abstract: Chronic exposure to stress or drugs of abuse has been linked to altered gene expression throughout the body, and changes in gene expression in discrete brain regions are thought to underlie many psychiatric diseases, including major depressive disorder and drug addiction. Preclinical models of these disorders have provided evidence for mechanisms of this altered gene expression, including transcription factors, but evidence supporting a role for these factors in human patients has been slow to emerge. The tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 50 publications
0
26
0
2
Order By: Relevance
“…c-Fos knockout mice exhibit significant learning impairment and hyperactivity (Velazquez et al, 2015 ). Meanwhile, downregulated FosB levels have been reported in the hippocampi of both depressed and addicted individuals (Gajewski et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…c-Fos knockout mice exhibit significant learning impairment and hyperactivity (Velazquez et al, 2015 ). Meanwhile, downregulated FosB levels have been reported in the hippocampi of both depressed and addicted individuals (Gajewski et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent post-mortem study showed that the expression of FosB isoforms was downregulated in the hippocampus of addicted patients ( Gajewski et al, 2016 ). Differently, we are here measuring in vivo FosB gene expression in PBLs.…”
Section: Discussionmentioning
confidence: 99%
“…The use of addictive drugs has been associated with alteration of gene expression in the brain that result in long-term changes on synapses and neural circuits and consequent neuroadaptive and behavioral changes such as tolerance and craving, which may underlie the development and maintenance of drug addiction ( Nestler, 2008 ; Gajewski et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Entre las consecuencias negativas derivables de la depresión se encontraría la drogodependencia o el consumo abusivo de sustancia. Si bien los mecanismos neurobiológicos y cognitivos que explican esta comorbilidad aún están siendo estudiados, existe mucha evidencia de la fuerte asociación entre la depresión y diversas problemáticas de consumo de drogas (Beaulieu, et al, 2018;Crnić, Todorović, Marković, Kastratović, y Timotijević, 2016;Gajewski, Turecki, y Robison, 2016;García-García, Luque, Santos Ruiz, y Tabernero, 2017;Gómez-Coronado, et al, 2018;Hammond, Lai, Wright, y Treisman, 2016;Khalid y Kausar, 2016;Hodgson, et al, 2017;Lai, Cleary, Sitharthan, y Hunt, 2015;Lister, Ledgerwood, Lundahl, y Greenwald, 2015;Rao, 2006). Una de las principales hipótesis que se han propuesto para la explicación de esta comorbilidad entre depresión y abuso de sustancia, es la hipótesis de automedicación (self-medication hypothesis; Gómez-Coronado, et al, 2018).…”
Section: Introductionunclassified